Heterodimer formation between thioredoxin f and fructose 1,6-bisphosphatase from spinach chloroplasts - Balmer, Yves; Schürmann, Peter (My University, 2001)
Chloroplast fructose 1,6-bisphosphatase (FBPase) is activated by reduction of a regulatory disulfide through thioredoxin f (Trx f). In the course of this reduction a transient mixed disulfide is formed linking covalently Trx f with FBPase, which possesses three Cys on a loop structure, two of them forming the redox-active disulfide bridge. The goal of this study was to identify the Cys involved in the transient mixed disulfide. To stabilize this reaction intermediate, mutant proteins with modified active sites were used. We identified Cys-155 of the FBPase as the one engaged in the formation of the mixed disulfide intermediate with Cys-46 of Trx f.
Keywords: Spinach; Fructose 1; 6-Bisphosphatase; Thioredoxin f; Site-directed mutagenesis; Intermolecular disulfide; Heterodimer